ANTIHYPERGLYCEMIC, ANTIOXIDANT, AND PANCREAS PROTECTIVE EFFECTS OF CORIANDRUM SATIVUM SEED IN ALLOXAN-INDUCED DIABETIC RATS - Widodo, Gunawan Pamudji; Handayani, Sri Rejeki; Hierowat, Rina (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2015)
Coriandrum sativum is a medicinal plant, used in traditional medicine for diabetes therapy. The goal of the this study was to determine the antidiabetic, antioxidant and pancreas protection effects of ethanol extracts of C. sativum seeds (CSE) in alloxan-induced diabetic rats. The male Wistar rats were induced diabetic by intraperitoneal injection of alloxan (150mg/kg BW). CSE was prepared and administrated orally to the animals at the dose of 125 and 250mg/kg for 28 days. Blood glucose level was measured, and antioxidant status was assessed by determining the activities of superoxide dismutase, glutathione peroxidase as well as malonyl aldehyde in liver. Histopathological study of pancreas was conducted at the end of experimental period. Both dose of SCE showed the glucose lowering effect, corrected antioxidant status of diabetic animals in liver and protected the pancreas organ from damage. Key words: Coriandrum sativum seed, antihyperglycemia, antioxidant, pancreas protection